Black empire : the masculine global imaginary of Caribbean intellectuals in the United States, 1914-1962 - Stephens, Michelle Ann, 1969- (New Americanists., 2005)
Expores the writings of Marcus Garvey, Claude McKay and C.L.R. James and argues that these black transnationals articulated a novel conception of black identity that reconfigures the meaning of American nationality.